The entrepreneurial group : social identities, relations, and collective action - Ruef, Martin (Kauffman Foundation series on innovation and entrepreneurship., 2010)
Recent surveys show that more than half of American entrepreneurs share ownership in their business startups rather than going it alone, and experts in international entrepreneurship have likewise noted the importance of groups in securing microcredit and advancing entrepreneurial initiatives in the developing world. Yet the media and many scholars continue to perpetuate the myth of the lone visionary who single-handedly revolutionizes the marketplace. The Entrepreneurial Group shatters this myth, demonstrating that teams, not individuals, are the leading force behind entrepreneurial startups.